MODERN APPROACH TO PROTECTION OF COMPUTER SYSTEMS AND NETWORKS - Dudykevych, Valerij; Piskozub, Andrian; Lomnytskyj, Igor (International Journal of Computing, 2014)
This article is dedicated to the use of firewalling method and intrusion detection method, which can be applied both separately and together to computer systems and networks, to expedience of the use of that or other method, tools, that perform these methods. We will try to carry out the analysis of the modern state of security questions in computer networks, to give recommendations how to attain the greatest level of protection of computer systems and networks by most effective way - within the shortest time interval, with minimum financial expenditures.